Realismo postdrammatico: 100% Karlsruhe dei Rimini Protokoll - Fiorentino, Francesco (Kritik. Rivista di letteratura e critica culturale, 2024)
The text proposes an analysis of the theatre of Rimini Protokoll by analysing certain performances, in particular 100% Karsruhe, which refer to political issues concerning participation and citizenship, representation and representativeness. Rimini Protokoll practise a postdramatic realism that has left behind the paradigm of representation and is marked by a particular dialectic of spectacularisation. It is a theatre that is realist because it exhibits the theatricality of existence, its ‘spectacularity’, but does not conceive the spectacle as a separation from real life, but rather as something that allows individuals to establish relationships with themselves and others. We are invited to conceive theatre not just as a medium through which life is articulated and interacts with itself, but also as a medium that allows us to establish contact with a real that resists theatricalisation, the articulation of life in terms of spectacle and staging.